Gih (Qi): Beyond Affordance - Lee, Yang; Shaw, Robert E.; Jin, Zheng (Frontiers in Psychology, 2017)
Ancient Eastern thought posited the ontological integration of the “mind-body world.” The body-mind syncretism was a foundational precept in Eastern philosophy in which ‘Gih’ (‘Qi’) was considered the basic entity of the universe and the human being. This study attempts to build a meta-theory and to provide empirical evidence for Gih, discussing the problems of the mind and body, or the subject and object, compared with the concept of “affordance” proposed by ecological approaches. The notion of Gih extends beyond that of affordance in that Gih activates a psychosomatic process between the physical condition and the mental state that facilitates the bi-directional interactions activation between subject and object. Therefore, the concept of Gih integrates mind and body, providing a means of comparing Eastern and Western philosophical systems.